An ethnographic study on the “Use of English Language by the Students of Grade nine” in a Private Boarding School of Chitwan - Ananta Dhungana, (Journal of Balkumari College, 2022)
English in Nepal is generally believed to be used only for international communication. The medium of instruction in private boarding schools is English & in most public schools are also practicing English medium classes. Most of the private schools have applied compulsory English language policy. English continues to play a crucial role in the communication among the students in those schools. This study has made an attempt to analyse the reason behind adopting compulsory English language policy and also tried to explore the trend of following the language policy by the students of grade nine. The study concludes that parents in particular and the society as a whole is responsible for the compulsory English language policy and the students of grade nine do not follow the school policy for exercising the freedom.